Short-term ozone exposure on stroke mortality and mitigation by greenness in rural and urban areas of Shandong Province, China - Ke Zhao; Fenfen He; Bingyin Zhang; Chengrong Liu; Yang Hu; Yilin Dong; Peiyao Zhang; Chao Liu; Jing Wei; Zilong Lu; Xiaolei Guo; Qing Huang; et al. (BMC, 2024)
Abstract Background Short-term exposure to ozone (O3) has been associated with higher stroke mortality, but it is unclear whether this association differs between urban and rural areas. The study aimed to compare the association between short-term exposure to O3 and ischaemic and haemorrhagic stroke mortality across rural and urban areas and further investigate the potential impacts of modifiers, such as greenness, on this association. Methods A multi-county time-series analysis was carried out in 19 counties of Shandong Province from 2013 to 2019. First, we employed generalized additive models (GAMs) to assess the effects of O3 on stroke mortality in each county. We performed random-effects meta-analyses to pool estimates to counties and compare differences in rural and urban areas. Furthermore, a meta-regression model was utilized to assess the moderating effects of county-level features. Results Short-term O3 exposure was found to be associated with increased mortality for both stroke subtypes. For each 10-µg/m3 (lag0-3) rise in O3, ischaemic stroke mortality rose by 1.472% in rural areas and 1.279% in urban areas. For each 0.1-unit increase in the Enhanced Vegetation Index (EVI) per county, the ischaemic stroke mortality caused by a 10-µg/m3 rise in O3 decreased by 0.60% overall and 1.50% in urban areas. Conclusions Our findings add to the evidence that short-term O3 exposure increases ischaemic and haemorrhagic stroke mortality and has adverse effects in urban and rural areas. However, improving greenness levels may contribute to mitigating the detrimental effects of O3 on ischaemic stroke mortality.